Self-healing and self-adhesive hydrogen gas sensing tape for robust applications - Yeasmin, Rubaya; Jung, Gwanggyo; Han, Seungik; Park, Chiwan; Seo, Hyungtak (Chemical Engineering Journal, 2024)
Chemochromic H2 gas sensing tape can be an ideal candidate for many robust applications because of its ease of use. The H2 gas sensing with self-healing and self-adhesive functionalities would add another degree of innovation. The current development is limited to noble metal-based and flexible sensors, while the self-healing and self-adhesive tape has not been explored widely. The objective of this paper is to develop a stretchable, self-healing and self-adhesive H2 gas sensing tape using Pd-WO3 chemochromic nanocomposites and PBS: Ecoflex hybrid polymer. The proposed development has been investigated using material and mechanical characterizations that ensure a high stretchability of 500 %, fast self-healing (in 30 s at room temperature), and excellent self-adhesive properties towards a variety of objects, including human skin, glass/plastic objects, stainless steel, gas cylinders, pipelines, and fittings. The optimized tape sensor is then tested in a real-application environment, where different concentrations of H2 were exposed to justify the chemochromic sensing performance. It is found that the sensor exhibits a rapid change in color from beige to blue with a maximum ΔE value of 40.28 in 10 s of H2 (100 %) exposure. The results are found very potential to be used in practical applications.
Keywords: Chemochromic; Hydrogen sensor; Self-adhesive tape; Self-healing; Stretchable